The Current Role of Carotid Duplex Ultrasonography in the Management of Carotid Atherosclerosis: Foundations and Advances - Kelly R. Byrnes; Charles B. Ross (International Journal of Vascular Medicine)
The management of atherosclerotic carotid occlusive disease for stroke prevention has entered a time of dramatic change. Improvements in medical management have begun to challenge traditional interventional approaches to asymptomatic carotid stenosis. Simultaneously, carotid artery stenting (CAS) has emerged as an alternative to carotid endarterectomy (CE). Finally, multiple factors beyond degree of stenosis and symptom status now mitigate clinical decision making. These factors include brain perfusion, plaque morphology, and patency of intracranial collaterals (circle of Willis). With all of these changes, it seems prudent to review the role of carotid duplex ultrasonography in the management of atherosclerotic carotid occlusive disease for stroke prevention. Carotid duplex ultrasonography (CDU) for initial and serial imaging of the carotid bifurcation remains an essential component in the management of carotid bifurcation disease. However, correlative axial imaging modalities (computer tomographic angiography (CTA) and contrast-enhanced magnetic resonance angiography (CE-MRA)) increasingly aid in the assessment of individual stroke risk and are important in treatment decisions. The purpose of this paper is twofold: (1) to discuss foundations and advances in CDU and (2) to evaluate the current role of CDU, in light of other imaging modalities, in the clinical management of carotid atherosclerosis.